Strengthening banking sector governance: challenges and solutions - Kawa Wali; Kees van Paridon; Bnar Karim Darwish (Future Business Journal)
Abstract This study examines the understanding of banking governance among the sample participants and its effectiveness in achieving significant objectives. The research methodology employed in this study adopts a descriptive and analytical approach, aiming to comprehensively examine the multifaceted phenomenon of corporate governance within the context of private banks. The purpose of this study was to assess the comprehension of banking governance and its effectiveness in achieving important objectives. This investigation was undertaken to gain insights into the current state of banking governance, its implementation, and the challenges it faces. By conducting this research, we aimed to provide a clearer understanding of the issues surrounding banking governance and offer recommendations for improvement and finding solutions. The findings of our study indicate that the sample participants have a clear comprehension of governance as an efficient system. However, we identified significant obstacles in the implementation of governance and its objectives, primarily stemming from legal challenges and the overall environment. We also noted that success for private banks is contingent on meeting governance requirements, but the banking sector faces challenges both internally and externally, which render control systems less effective. Furthermore, we found that the Basel standards for banking supervision, through the implementation of supervision and control procedures, seek to enhance solvency and risk management, along with prudential measures. These findings are crucial as they provide a roadmap for strengthening governance practices in the banking sector, which is vital for its stability and effective operation. By addressing the issues identified in this study, stakeholders can work toward achieving a more robust and effective banking governance framework.Please confirm if the author names are presented accurately and in the correct sequence (given name, middle name/initial, family name). Author 2 Given name: [Kees] Particle [van] Last name [Paridon]. Author 3 Given name: [Bnar Kareem] Last name [Darwish]. Also, kindly confirm the details in the metadata are correct.correct